A 3D Platform to Investigate Dynamic Cell-to-Cell Interactions Between Tumor Cells and Mesenchymal Progenitors - Golinelli, Giulia; Talami, Rebecca; Frabetti, Stella; Candini, Olivia; Grisendi, Giulia; Spano, Carlotta; Chiavelli, Chiara; Arnaud, Gaëlle F.; Mari, Giorgio; Dominici, Massimo (Frontiers in Cell and Developmental Biology, 2022)
We here investigated the dynamic cell-to-cell interactions between tumor and mesenchymal stromal/stem cells (MSCs) by the novel VITVOⓇ 3D bioreactor that was customized to develop in vivo-like metastatic nodules of Ewing’s sarcoma (ES). MSCs are known to contribute to tumor microenvironment as cancer associated fibroblast (CAF) precursors and, for this reason, they have also been used as anti-cancer tools. Using dynamic conditions, the process of tissue colonization and formation of metastatic niches was recreated through tumor cell migration aiming to mimic ES development in patients. ES is an aggressive tumor representing the second most common malignant bone cancer in children and young adults. An urgent and unmet need exists for the development of novel treatment strategies to improve the outcomes of metastatic ES. The tumor-tropic ability of MSCs offers an alternative approach, in which these cells can be used as vehicles for the delivery of antitumor molecules, such as the proapoptotic TNF-related apoptosis inducing ligand (TRAIL). However, the therapeutic targeting of metastases remains challenging and the interaction occurring between tumor cells and MSCs has not yet been deeply investigated. Setting up in vitro and in vivo models to study this interaction is a prerequisite for novel approaches where MSCs affinity for tumor is optimized to ultimately increase their therapeutic efficacy. Here, VITVOⓇ integrating a customized scaffold with an increased inter-fiber distance (VITVO50) was used to develop a dynamic model where MSCs and tumor nodules were evaluated under flow conditions. Colonization and interaction between cell populations were explored by droplet digital PCR (ddPCR). VITVO50 findings were then applied in vivo. An ES metastatic model was established in NSG mice and biodistribution of TRAIL-expressing MSCs in mice organs affected by metastases was investigated using a 4-plex ddPCR assay. VITVOⓇ proved to be an easy handling and versatile bioreactor to develop in vivo-like tumor nodules and investigate dynamic cell-to-cell interactions with MSCs. The proposed fluidic system promises to facilitate the understanding of tumor-stroma interaction for the development of novel tumor targeting strategies, simplifying the analysis of in vivo data, and ultimately accelerating the progress towards the early clinical phase.